Complexity algorithm analysis for edit distance - Maarif, Haris Al Qodri; Akmeliawati, Rini; Htike@Muhammad Yusof, Zaw Zaw; Gunawan, Teddy Surya (2014)
Natural Language Processing (NLP) is a method which works on any language processing. Some of the algorithms are based on edit distance analysis. It is a process where the statistical calculations between two words or sentences are analyzed. Some of used edit distances for NLP are Levenshtein, Jaro Wrinkler, Soundex, N-grams, and Mahalanobis. The evaluation of edit distance is aimed to analyze the processing time of each edit distance in calculation of two different words or sentences. The objective of this paper is to evaluate the complexity of each distance, based on the time process.